Towards Digital Histories of Women’s Suffrage Movements: A Feminist Historian’s Journey to the World of Digital Humanities - Heidi Kurvinen (Helsinki University Press, 2022)
This chapter discusses the various practical, epistemological and methodological issues of importance when a historical scholar with limited digital skills wants to take a step towards learning how to conduct digital analyses. As a feminist historian, the author combines this approach with a discussion of the relation of feminist research and digital humanities. In line with practice in feminist research, she uses a self-reflexive approach and asks how the increase in the understanding of digital methods influences research questions in feminist history. Do digital humanities tools transform the work as feminist historians? How can digital analyses develop the field of gender history in general and the history of feminism in particular? Can a scholar who has limited technological skills engage with an informed and critical discussion with digitised materials? In doing this the chapter provides an inside reflective history of the making of digital history.
Digital Histories: Emergent Approaches within the New Digital History